2006
DOI: 10.1159/000093530
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphology of the Avian Cerebellum: I. Degree of Foliation

Abstract: Despite the conservative circuitry of the cerebellum, there is considerable variation in the shape of the cerebellum among vertebrates. One aspect of cerebellar morphology that is of particular interest is the degree of folding, or foliation, of the cerebellum and its functional significance. Here, we present the first comprehensive analysis of variation in cerebellar foliation in birds with the aim of determining the effects that allometry, phylogeny and development have on species differences in the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 115 publications
2
99
2
2
Order By: Relevance
“…Considering only primates (35) or a smaller but diverse set of mammals (36), both absolute and relative brain sizes contribute to gyrification. In birds, "foliation," or the amount of folding in the cerebellum, is similarly related to both the absolute size of the cerebellum and its relative size compared with the medulla (40).…”
Section: Discussionmentioning
confidence: 99%
“…Considering only primates (35) or a smaller but diverse set of mammals (36), both absolute and relative brain sizes contribute to gyrification. In birds, "foliation," or the amount of folding in the cerebellum, is similarly related to both the absolute size of the cerebellum and its relative size compared with the medulla (40).…”
Section: Discussionmentioning
confidence: 99%
“…Many other species have more foliated cerebella (e.g., fig. 3 D, I, K, L), but these are generally larger birds, as the degree of foliation is correlated with cerebellar volume, brain volume and body mass [Iwaniuk et al, 2006c]. This is best demonstrated within the Corvida ( fig.…”
Section: Phylogenetic Effectsmentioning
confidence: 91%
“…Larsell [1967] defined individual folia and their subdivisions based upon cerebellar development in chickens (Gallus domesticus) and ducks (Anas platyrhynchos) and extrapolated this to other species. This is problematic, however, because there are species differences in how the cerebellum develops [Larsell 1967] and the pattern of cerebellar development is unknown for For further details regarding the sources of these specimens, see Iwaniuk et al [2006c].…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a previously devised visual grading schema on a scale of 1-5 , the folding of the corpus has been visually quantified in the deep-sea sharks and holocephalans in this study, and the foliation index gradings were found to range from 1 to 2 ( table 1 ). Foliation of the cerebellum has been studied in a number of other vertebrate groups, including birds [Senglaub, 1963;Larsell, 1967;Pearson and Pearson, 1976;Iwaniuk et al, 2006Iwaniuk et al, , 2007 and mammals [Zilles et al, 1989;Striedter, 2005], and has been correlated with behavioral specializations and cognitive capabilities across these clades [Butler and Hodos, 1996]. Low foliation levels in these deep-sea fishes have been linked to lower activity levels and a close association to the substrate [Northcutt, 1989;Yopak and Frank, 2007;, in addition to less active predation strategies in a 2-dimensional environment [Yopak and Frank, 2007;.…”
Section: Brain Organizationmentioning
confidence: 99%